Dysarthria: Definition, clinical contexts, neurobiological profiles and clinical treatments - Perrotta, Giulio (Archives of Community Medicine and Public Health, 2020)
Starting from the general concept of Dysarthria, the present work focuses on the clinical, neurobiological, and functional aspects of the morbid condition, suggesting a multidimensional treatment between physiotherapy, psychotherapy, and rehabilitation exercises for lost skills.